China's contribution to the fight against the COVID-19 epidemic (International relations and international law Journal, 2022)
The new coronavirus at the end of 2019 is the common enemy of all mankind. The rapid spread ofthe COVID-19 pandemic poses a huge challenge to global public health security. At present, globalizationgoes far beyond economic activity and embraces the political, cultural, environmental and healthsecurity spheres. Deepening globalization has led to an unprecedented acceleration in the movementof goods and people across borders, and the growth of international trade and tourism in particularhas made it extremely easy for infectious diseases to spread beyond individual countries and regions,resulting in widespread international transmission. Therefore, infectious diseases are no longer a matterof individual national or regional control, and sovereign states cannot respond to public health challengeswith unilateral action alone. In the face of an increasingly serious global pandemic, there is broadconsensus that the international community is working together to fight the pandemic. Fighting the pandemicis a double test of the ability of sovereign nations to govern and participate in global governance.Since the spread of the COVID-19 pandemic, China has taken the most comprehensive, rigorous, andmeticulous measures to establish a “first line of defense” against the COVID-19 pandemic.Key words: Chinese model, pandemic, fighting the COVID-19, humanitarian aid.